The Stable Equilibrium Analysis of Nonlinear Renewable Resource Stock Evolution. (22nd March 2023) - Güven, Gökhan; İnançli, Selim
Abstract : This paper provides the formal proofs of propositions concerning the stability analysis of steady-state equilibrium in autarky with open-access renewable resources. We assume three different resource environments in which excessive harvesting, pollution, and simultaneous coexistence of these interacting pressures on resource stocks are considered. The propositions mentioned on J.A. Brander and M.S. Taylor, Open access renewable resources: trade and trade policy in a two-country model, Journal of International Economics, 44 (2), 181–209, 1998; B.R. Copeland and M.S. Taylor, Trade, spatial separation, and the environment, Journal of International Economics, 47 (1), 137–168, 1999; and H. A. Rus, Renewable resources, pollution and trade, Review of International Economics, 24 (2), 364–391, 2016 have been shown only on the diagrams and also implicitly explained. This paper aims to contribute the renewable open-access resources literature by providing formal solutions of stable equilibrium analysis in a closed economy within the long run.